Valor nutritivo e cinética da digestão de silagens de genótipos de sorgo de diferentes propósitos cultivados em primeira safra no norte de Mato Grosso - Souza, Juliana Maria Silva de (2021)
Due to the growing demand for bulky foodstuffs for animal production, there is a need to develop and identify sorghum cultivars with a view to producing silage with good nutritional value. In this context, the objective was to evaluate the characteristics of silages of 15 sorghum genotypes for different purposes, aiming to identify new materials with potential to be released on the market and suitable for recommendation for the production of quality silages in northern Mato Grosso. The experiment was carried out at Embrapa Agrossilvipastoril and at UFMT in Sinop/MT. Different genotypes were evaluated, regarding the loss characteristics and fermentative profile of the silage, chemical composition, gas production (PG) and in vitro digestibility and the energy estimate of the silages. Fifteen genotypes were evaluated, the forages BRS 658, BRS 659, Volumax, BRS Ponta Negra, 15F30005 and 15F30006, saccharine BRS 511, CMSXS 5027, 5030, 5043 and 5045 and biomass 201934B008, AGRI-002E, BRS 716 and CMSXS 7501 bmr. The BRS Ponta Negra, BRS 511, CMSXS 5030, CMSXS 5043 and CMSXS 7501 had lower pH, with an average of 3.73. The highest crude protein content was from BRS 658 and BRS 659, 78.1 g kg-1 DM. BRS 659 and CMSXS 5027 had lower neutral detergent insoluble fiber content with 389.4 g kg-1 DM. For GP, BRS 658, BRS 659, Volumax, BRS Ponta Negra, 15F30005, 15F30006, BRS 511, CMSXS 5027, CMSXS 5030 and CMSXS 5043 had the highest mean, 195.75 mL g-1 MS. All genotypes evaluated in this study have adequate characteristics for fermentation profile. As for the nutritional value and energy potential, the best materials are the commercial BRS 658, BRS 659, BRS Ponta Negra and Volumax, and the experimental 15F30006, CMSXS 5027 and CMSXS 5030. The use of biomass material silages is an alternative for systems that they need bulky feed in high quantities, due to their high production of dry mass per ha.